2001
DOI: 10.1046/j.1440-1746.2001.02464.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of endoscopic reflux esophagitis among Koreans

Abstract: The prevalence of endoscopic reflux esophagitis among Koreans is 3.4%, and most of the patients had a mild grade esophagitis. Smoking, alcohol consumption, the presence of a hiatal hernia and a higher BMI are associated with the development of reflux esophagitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
62
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 15 publications
12
62
2
Order By: Relevance
“…With the increased prevalence of metabolic syndrome, GERD has also become more prevalent in Korea. The overall prevalence of erosive esophagitis was 3.4% in 2001 [21] and 6.6% in 2006 [6] . In terms of reflux symptoms, 2.5% of adults experienced heartburn and reflux symptoms in 2000 [22] .…”
Section: Discussionmentioning
confidence: 98%
“…With the increased prevalence of metabolic syndrome, GERD has also become more prevalent in Korea. The overall prevalence of erosive esophagitis was 3.4% in 2001 [21] and 6.6% in 2006 [6] . In terms of reflux symptoms, 2.5% of adults experienced heartburn and reflux symptoms in 2000 [22] .…”
Section: Discussionmentioning
confidence: 98%
“…8 In a 1994 Korean study, an overall prevalence of erosive esophagitis was 2.4%, 18 which 20 The prevalence increased over the past 10 years. [5][6][7][8][9][18][19][20] Kawaguchi et al 4 reported that the prevalence of GERD in CKD patients increases probably due to increased gastrin secretion, decreased H. pylori prevalence, and interference with gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…Erosive esophagitis was positively related to alcohol consumption [28] . The mechanism is that alcohol intake induces nausea and vomiting and directly causes mucosal impairment, while food intake at late night elevates the risk of esophagitis [29] .…”
Section: ) Patientsmentioning
confidence: 94%